HELPING MARRIAGES THAT SUFFER FROM RELATIONSHIP PROBLEMS: A COGNITIVE BEHAVIOURAL SYSTEMS APPROACH - (:unkn) unknown (INT INST ADVANCED STUDIES PSYCHOTHERAPY & APPLIED MENTAL HEALTH, 2016)
The path to achieving the knowledge and skills necessary to become a competent coach to help couple and relationship problems is diverse. A good coach is expected to gather enough data to make a good conceptualization of the case in order to understand and pinpoint the interactional patterns of the couple relationship that are dysfunctional and require special attention. After understanding the specific needs of the couple, an approach that is geared and tailored according to the particular needs of the couple must be taken. This paper aims to describe the basic components of the cognitive and behavioral approach and some concepts from the systems approach that are found useful to integrate with the cognitive behavioral approach. The cognitive behavioral approach can be said to be reliable method in helping many couples and despite inadequate research systems approach are increasingly used by experienced professionals to offer a new perspective which might be called as cognitive behavioral systems approach.
Keywords: couple and relationship problems; Cognitive Behavioral Couple Approach; Systems Approach to couple problems; Cognitive Behavioral Systems Approach to couple problems; MARITAL-THERAPY; DEPRESSION; COUPLE; INTERVENTIONS; RECIPROCITY